Sustainable green campus in Nepal: 3E analysis - Yadav, B. K.; Rauniyar, P. K.; Sudhakar, K.; Bajracharya, T. R.; Priya, S. S. (Oxford University Press, 2021)
In today's world, where global warming is one of the greatest human challenges, sustainable energy generation is becoming increasingly relevant. The use of green and clean energy sources is the best way to minimize CO2, CO, NOX and other emissions of conventional energy usage. Solar photovoltaic (PV) systems are more beneficial and an exciting application to set up an eco-friendly green educational campus. In this regard, the potential sites within Tribhuvan University, Institute of Engineering, Purwanchal Campus, Dharan city, Nepal are analysed for grid-tied solar PV power plant installation to meet the 100% energy demand of the campus using energy, economic and environment-friendly analysis. The daily, monthly and annual load and solar irradiance data of past years of the campus have been analysed to estimate the solar PV plant's capacity and system performance using PVSYST V7.0 software analysis tools. The simulation results show that 110 kWp of solar PV power plant will be sufficient for the entire campus to qualify for the first fully green-powered campus in Nepal, which corresponds to fulfill 66.4 MWh/year daytime energy demand out of total 161 MWh/year energy consumption of the campus with a capacity to generate a total of 181.5 MWh/year energy from the designed solar PV system. The result also shows that 115.1 MWh/year of surplus energy produced from the PV power plant can be injected into the utility grid to yield considerable savings in utility cost. On the basis of these results, campus authorities and stakeholders may commit to investing and implementing of this project to ensure that the campus is completely green.